An application of the modified total factor productivity measurement (TFPM) model in the Cebu rattan and wood furniture industry - Leath, Delia Alota (Animo Repository, 2002)
This study focus on the development of a Total-Factor Productivity Measurement (TFPM) application in the Cebu rattan and wood furniture industry. Emphasis was given on the identification of the information needs of managers relative to productivity improvement and of the productivity measurement techniques currently employed by the industry. A total of seven respondent companies were considered in the study. The information needs identified from the respondents were : (1) productivity performance per operation (2) productivity analysis per product model and per customer (3) productivity of labor and materials (4) performance measures that will point to priority areas for improvement (5) measurement and evaluation of past performance and (6) productivity of operations and aggregating measures to overall firm. Total output criterion and the cost analysis approach, the two productivity measurement techniques presently employed were rendered deficient in addressing the information needs of managers in making decisions and initiating actions for productivity improvement. The review on the available productivity measurement technologies in the literature, revealed that TFPM is state-of-the-art in measuring productivity as evidenced by more than 13 versions in the literature with later versions becoming more complex for first-time users. The teaching TFPM model of Dr. Pineda was considered as a simple model to start an initial application with using an Excel based spreadsheet format and is currently being push by PDC-DAP. However, the model has certain weaknesses, such as : no column labels for inputs, absence of mathematical portrayals, performance indices expressed in decimal numbers, and TFPM data not being used as basis for gainsharing. Hence, the main output of the study is a modified TFPM model that addresses the identified information needs of managers and eliminates the weaknesses through the incorporation of the desirable features from the other models.